Variability in seed oil content, fatty acids profile, phytochemical properties, mineral and proximate composition of Iranian cultivars of vitis vinifera L - Fateme Poureshaghi; Ghasem Eghlima; Deniz Khanmohammadi; Hassan Esmaeili; Mohammad Hossein Mirjalili (Scientific Reports)
Abstract Vitis vinifera L., a significant fruit species within the Vitaceae family, is extensively cultivated globally and finds diverse applications across the pharmaceutical, cosmetic, and food sectors. Notably, grape seeds are abundant in oils, phenolic compounds, and essential minerals, which may confer various health benefits. To enhance the value and optimize the use of grape seeds, recognized as a significant byproduct in industrial applications, this research investigated and compared ten Iranian grape cultivars regarding their oil content and composition, phenolic compounds, antioxidant properties, mineral content, and proximate analysis. The seed oil content ranged from 4.03 to 18.01%. The primary fatty acids identified in these cultivars were linoleic acid (varied from 17.9 to 59.4%) and margaric acid (from 1.6 to 33.2%). The seed oils were found to be rich in polyunsaturated fatty acids (PUFAs), which comprised between 17.9% and 62.1% of the total fatty acids, while monounsaturated fatty acids (MUFAs) and saturated fatty acids (SFAs) were present in proportions of 3.7–16.8% and 20.9–78.4%, respectively. The analyzed cultivars exhibited variations in carbohydrate (19.23 to 25.37 g/100 DW), fat (10.24 to 13.72 g/100 DW), protein (9.62 to 14.63 g/100 DW), and fiber (38.41 to 42.87 g/100 DW) contents. Notable mineral elements such as potassium (3.82–8.34 mg/g DW), phosphorus (2.34–3.74 mg/g DW), calcium (1.05–2.31 mg/g DW), magnesium (0.23–1.42 mg/g DW), and iron (0.01–0.03 mg/g DW) were detected across the cultivars analyzed. The primary phenolic compounds identified included gallic acid, quercetin, and kaempferol. Hosseini and Rashmiri cultivars were superior in terms of seed oil content and phenolic compounds, respectively. The significant variation observed among the different grape varieties concerning oil content and composition, phytochemical profiles, mineral content, and proximate composition indicates their potential as valuable sources of oil and nutritional components for application in food and cosmetic industries.